PENERAPAN FUZZY INFERENCE SYSTEM DENGAN METODE FUZZY TSUKAMOTO PADA SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN KARYAWAN - Tri Akhyari Romadhon; Fandi Kurniawan; Ruliansyah Ruliansyah; Evi Fadilah (Sienna, 2022)
Companies must pay attention to the criteria or standards that have been set to improve the quality of employee recruitment. however, atl PT. Sinarl Sosro KPBl Palembang, hiring is stilll subjective and can only be seen from the test results. lTherefore, itl is necessaryl to create al decision supportl system usingl the Tsukamotol fuzzy methodl which canl assist decisionl makers inl obtaining informationl for selecting prospectivel employees. The system development methodl used means Prototype. Thel programming languagel used isl Hypertext Preprocessorl (lPHP), andl the databasel uses lMySQL, and thel testing methodl uses Blackboxl testing.